En busca de la poesía oculta en las márgenes (2021)
Several phenomena such as mystical, indigenous and Afro-descendant poetry have been discovered (and rediscovered) in a project of the Department of Humanities that investigates poets and creations that were left out of the prevailing aesthetic canons in Colombia. This is the project From the Canon to the Margins: A Critical Study of Poetry in Colombia in the 20th Century, directed by professors Alejandra Toro Murillo and Juan Manuel Cuartas Restrepo.